Performance and parameter sensitivity comparison of CSP power cycles under wide solar energy temperature ranges and multiple working conditions. (15th August 2020) - Zhai, Huixing; Wang, Suilin; An, Baolin; Dai, Xiaoye
Highlights: S-CO2 Brayton cycle has the highest efficiency for 500–1000 °C solar temperatures. The lowest P tur_in of the cycle for ' η max -1%' is much lower than P tur_in for η max. S-CO2 Brayton cycle is severely undervalued if P tur_in is restricted to 30 MPa. Air Brayton cycle does not need high P tur_in but 6% lower than s-CO2 efficiency. Sensitivity to η tur is air Brayton cycle > steam Rankine cycle > s-CO2 Brayton cycle. Abstract: Concentrated solar power (CSP) is an important way for solar energy utilization, and the efficient solar energy utilization is closely related to a reasonable power cycle. The comparative analysis of the steam Rankine cycle, supercritical CO2 (s-CO2 ) Brayton cycle and air Brayton cycle is always with a particular heat source, working parameter and working condition. However, the solar energy for CSP has a wide temperature range from 250 to 1000 °C and the energy conversion potential of the cycles varies obviously under different heat source temperatures. The maximum pressure of the working condition restricts the cycle energy conversion potential especially for s-CO2 Brayton cycle. The isentropic efficiency settings severely influence on the cycle comparison results. Therefore, in this work, the energy conversion mechanism and potential of the three types of cycles under a wide solar energy temperature ranges are revealed by optimized with multi-operating conditions. The sensitivity of each cycle to the high working pressure and irreversible processes are analyzed. Results show that, achieving the highest efficiency η max often means an extremely high working pressure. However, the lowest P tur_in to keep relatively high efficiency (higher than ' η max -1%') can be much lower than that of the maximum efficiency. S-CO2 Brayton cycle has the absolutely highest cycle thermal efficiency when the turbine inlet temperature is higher than 500 °C and the least sensitive to the turbine isentropic efficiency. However, s-CO2 Brayton cycle is the most dependent on high turbine inlet pressure and the energy conversion potential of s-CO2 Brayton cycle is severely undervalued if the working pressure is restricted to 20 MPa or 30 MPa. The air Brayton cycle efficiency keeps around 6% lower than the s-CO2 Brayton cycle at the same turbine inlet temperature and exceed the steam Rankine cycle when the turbine inlet temperature is higher than 750 °C. The air Brayton cycle has the least dependence on high working pressure, however, it is most affected by the non-ideality of expansion and compression processes.